THE ROLE OF PEER INTERACTION IN LANGUAGE LEARNING AMONG TEENAGERS (SCIENCE TIME JOURNAL, 2026)
This article examines the role of peer interaction in language learning among teenagers, focusing on its influence on language acquisition and social skills development. The aim of the paper is to analyze how collaborative interactions among peers can enhance language learning experiences and outcomes. A mixed-methods approach was employed, involving a questionnaire and interviews with students. The results reveal that peer interaction significantly contributes to improved language proficiency, increased motivation, and reduced anxiety in language learning contexts. Furthermore, students reported that collaborative activities, such as group discussions and peer teaching, facilitated a deeper understanding of language concepts. The study concludes that integrating peer interaction into language learning strategies is crucial for fostering effective communication skills and promoting a supportive learning environment among teenagers.